Private credit in 129 countries☆ - DJANKOV, S; MCLIESH, C; SHLEIFER, A (Journal of Financial Economics, 2007)
We investigate cross-country determinants of private credit, using new data on legal creditor rights and private and public credit registries in 129 countries. Both creditor protection through the legal system and information-sharing institutions are associated with higher ratios of private credit to gross domestic product, but the former is relatively more important in the richer countries. An analysis of legal reforms shows that credit rises after improvements in creditor rights and in information sharing. Creditor rights are remarkably stable over time, contrary to the hypothesis that legal rules are converging. Finally, legal origins are an important determinant of both creditor rights and information-sharing institutions. The analysis suggests that public credit registries, which are primarily a feature of French civil law countries, benefit private credit markets in developing countries.